PENGARUH PENGENALAN LAPANGAN PERSEKOLAHAN, PERSEPSI PROFESI GURU DAN EFIKASI DIRI TERHADAP KESIAPAN MENJADI GURU: (Survei Pada Mahasiswa PPG Prajabatan Universitas Siliwangi Tahun 2024) - Gita Sherly; Edi Fitriana Afriza; Rendra Gumilar (Universitas Muhammadiyah Metro, 2025)
The quality of education is strongly influenced by the readiness of teachers in carrying out their professional duties. Low levels of readiness among students in entering the teaching profession may negatively impact future educational outcomes. This study aims to analyze the influence of School Field Introduction (Pengenalan Lapangan Persekolahan), perceptions of the teaching profession, and self-efficacy on the readiness of Pre-service Teacher Professional Education (PPG Prajabatan) students at Universitas Siliwangi in 2024 to become professional teachers. This research employed a quantitative approach using a survey method with an explanatory research design. The study population consisted of 374 students, and a sample of 193 students from waves 1 and 2 was selected through random sampling. Data were collected through online questionnaires using Google Forms and analyzed using multiple linear regression with SPSS version 25. The results showed that all three independent variables School Field Introduction, perception of the teaching profession, and self-efficacy had a positive and significant effect on students' readiness to become teachers, both partially and simultaneously. These findings emphasize the importance of strengthening field practice experiences, fostering positive perceptions of the teaching profession, and enhancing self-efficacy within the PPG program. This study contributes to the body of knowledge by providing empirical evidence on the factors influencing teacher readiness, which can inform policy improvements and the future implementation of teacher education programs